The Fabrication and Characterization of Piezoelectric PZT/PVDF Electrospun Nanofiber Composites - Ji Sun Yun; Chun Kil Park; Young Hun Jeong; Jeong Ho Cho; Jong-Hoo Paik; Sun Hong Yoon; Kyung-Ran Hwang (Nanomaterials and Nanotechnology)
Piezoelectric nanofiber composites of polyvinylidene fluoride (PVDF) polymer and PZT (Pb(Zr0.53Ti0.47)O3) ceramics were fabricated by electrospinning. The micro‐ structure of the PZT/PVDF electrospun nanofiber compo‐ sites was characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The tensile properties (stress- strain curves) and electrical properties (P-E hysteresis loops) of the PZT/PVDF electrospun nanofiber composites were investigated as a function of PZT content from 0 wt% to 30 wt%. The results demonstrated that a PZT content of 20 wt % had enhanced tensile and piezoelectric characteristics.